Design and simulation of a lumped element metal finger capacitor for RF-CMOS power splitters - Uddin, Md. Jasim; Nordin, Anis Nurashikin; Ibrahimy, Muhammad Ibn; Reaz, Mamun Bin Ibne (2010)
Design, development and simulation results of an interdigitated metal-fingers capacitors in 0.18 #x03BC;m RF-CMOS technology that are exploiting both lateral and vertical metal-metal capacitances are presented. Two RF-CMOS capacitors are designed specifically for applications in a 2.45GHz power splitter circuit. Five metal RF-CMOS layers are used to design two capacitors of 1.39pF and 2.2pF, consisting of 101 and 105 metal fingers respectively. The real impedance obtained at the input is Z1 = 35.04 #x03A9; and Z2 = 39.73 #x03A9;, while the insertion loss is S21 = 2.47dB. Return loss S11 and S22 are simulated as 4.042dB and 4.047dB respectively. Phase measurements of 110.9 #x00B0; and 101.2 #x00B0; are obtained for the input and output ports, indicating that the phase shift is not degraded too much due to the capacitor.